Event risks and scenarios for the 1999 Paddington accident - Voloshyn, V.S. (Reporter of the Priazovskyi State Technical University Section Technical sciences, 2024)
The accident near London in October 1999 didn't just shocks the UK. The collision of the two trains showed the obvious inadequacy of the existing models of train control on the Great Western main line of the UK railways. Specialists from a wide variety of fields of knowledge repeatedly return to this problem, trying to find key ways to minimize risks in this very difficult transportation industry. In this paper, an attempt is made to create a model NS neural network, which makes it possible to predict the possible consequences of a variety of technologically programmed actions, and safe dispatching. The five-sync model is based on all known risk-forming events that contributed to the occurrence of an accident in one way or another. As a function of synapse neuron activation, the bifurcation dependence of the doubled accounting period was chosen due to the number and uncertainty of the content of the accounting indicators that affect the final result. This made it possible to take into account the uncertainties that accompany the occurrence of any intersynapse channels from each input event to the resulting protocol, which assumes only a binary mapping of the expected risk. Thanks to this model, potential and hidden sources of potential risks for any system of events equivalent to the Paddington system are identified, taking into account some of its drawbacks. It is shown that the prevention of such accidents using neural network models should is reduced to automatically tracking images of potential risk-forming events embedded in the trained NS and alerting at least one or two of the monitored ones. It should be noted that such an NS model can be useful not only for the conditions of the Great Western Main Line of the UK railways, but for other systems that are subject to the same operating rules as in our example Аварія під Лондоном у жовтні 1999 року шокувала не лише Велику Британію. Зіткнення двох поїздів показало очевидну неадекватність існуючих моделей управління поїздами на Великій Західній головній лінії залізниць Великобританії. Фахівці найрізноманітніших галузей знань неодноразово повертаються до цієї проблеми, намагаючись знайти ключові шляхи мінімізації ризиків у цій дуже складній транспортній галузі. У даній роботі зроблена спроба створення моделі нейронної мережі NS, що дає можливість прогнозувати можливі наслідки різноманітних технологічно запрограмованих дій і безпечну диспетчеризацію. В основі п'ятисинапсної моделі, що запропоновано, згруповані всі відомі ризикоутворюючі події, які так чи інакше сприяли виникненню аварії. Як функцію активації нейронів синапсів обрано біфуркаційну залежність подвоєного облікового періоду за рахунок кількості та невизначеності змісту облікових показників, що впливають на кінцевий результат. Це дозволило врахувати невизначеності, які супроводжують активність будь-яких міжсинапсних каналів від кожної вхідної події до кінцевого протоколу, який приймає лише бінарне представлення очікуваного ризику. Завдяки цій моделі, виявляються як наочні, так і приховані джерела потенційних ризиків для будь-якої системи подій, еквівалентних Паддінгтонській системі, з урахуванням деяких її недоліків. Показано, що запобігання таких аварій за допомогою моделей нейронних мереж має зводитися до автоматичного відстеження відображень потенційних ризикоутворюючих подій, вбудованих у навчену NS, і оповіщення принаймні одного або двох з таких, що відстежуються. Слід зазначити, що така модель NS може бути корисною не тільки для умов Великої Західної Головної Лінії залізниць Великобританії, але і для інших систем, на які поширюються ті ж правила експлуатації, що і в нашому прикладі